2015
DOI: 10.5539/elt.v8n11p28
|View full text |Cite
|
Sign up to set email alerts
|

Secondary School Students’ Reading Anxiety in a Second Language

Abstract: Developing an appropriate competence in reading in English as a second language is a key factor for subsequent academic success. This study investigated second language reading anxiety of secondary school students. A questionnaire was distributed to 72 female students and focus-group interviews were conducted with 19 volunteer students. Overall results reveal significant differences between the levels of reading anxiety reported by students relative to their general area of study (viz., science or arts). All t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 28 publications
(40 reference statements)
1
5
0
2
Order By: Relevance
“…The variable of branch of study was taken into consideration by some researchers who investigated foreign language reading anxiety. Ismail (2015), which was conducted among secondary school female students in UAE, showed that there is a significant difference in reading anxiety between students of science and students of arts, in favor of science students. He also added that vocabulary and grammatical knowledge are sources of reading anxiety.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The variable of branch of study was taken into consideration by some researchers who investigated foreign language reading anxiety. Ismail (2015), which was conducted among secondary school female students in UAE, showed that there is a significant difference in reading anxiety between students of science and students of arts, in favor of science students. He also added that vocabulary and grammatical knowledge are sources of reading anxiety.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Similarly, Ahmed Ismail (2015) scrutinized second language reading anxiety of secondary school students. Overall outcomes reveal signi cant dissimilarities among the levels of reading anxiety reported by students relative to their general area of study (viz., science or arts).…”
Section: Foreign Language Reading Anxiety (Flra)mentioning
confidence: 99%
“…Öğrencilerin; okuma esnasında kendilerini ne kadar stres ve baskı altında hissederlerse, okuduğunu anlama performanslarının da o kadar olumsuz olabileceğine dikkat çekmektedir. Ahmed Ismail (2015) ikinci dil olarak İngilizceyi ve ana dili Arapça olan ortaokul öğrencilerinin okuma kaygılarını incelemiştir. Öğrencilerdeki okuma kaygısının altında yatan nedenlerin dil yeterliliğine, dilbilgisi kurallarına ve özellikle de kelime bilgisine dayalı olduğunu belirtmektedir.…”
Section: Araştırma Makalesiunclassified